Knowledge and practices related to the use of personal audio devices and associated health risks among medical students in Delhi - Saurav Basu; Suneela Garg; M Meghachandra Singh; Charu Kohli (Wolters Kluwer Medknow Publications, 2019)
BACKGROUND: Over 1 billion young people globally are at risk of hearing loss and road traffic accidents due to unsafe listening practices while using personal audio devices (PADs). Rapid proliferation of mobile phones with built-in music playback facility has rendered nearly universal PAD access. The objective of this study was to ascertain the knowledge of risks and patterns of usage of PADs among medical undergraduate students in Delhi, India. MATERIALS AND METHODS: A cross-sectional study was conducted among medical students] aged ≥18 years. Data were collected using a pretested self-administered questionnaire during December 2016-May 2017. Chi-square test was used to find an association between the categorical variables. RESULTS: A total of 255 male and 133 female students were enrolled (n = 388). Male students used PADs with greater frequency and perceived lesser susceptibility to adverse health effects on prolonged PAD usage compared to female students. However, volume preference for PAD usage did not vary across gender. Self-reported history of hearing loss and tinnitus which persisted for at least 3 days in the previous 6 months was 10.6% and 6.4%, respectively. Nearly one in ten students agreed to the possibility of crossing the road while listening to music on their PADs. DISCUSSION: Unsafe music-listening practices using PADs is potentially compromising the health and safety of young people in India. Strategic approaches supporting information education communication activities for promoting awareness of hearing and health risks related to prolonged PAD use at loud volumes and enactment of policies restricting undesirable PAD usage threatening road safety need consideration.